2023
DOI: 10.1007/s13311-022-01323-7
|View full text |Cite
|
Sign up to set email alerts
|

Activities of (Poly)phenolic Antioxidants and Other Natural Autophagy Modulators in the Treatment of Sanfilippo Disease: Remarkable Efficacy of Resveratrol in Cellular and Animal Models

Abstract: Sanfilippo disease, caused by mutations in the genes encoding heparan sulfate (HS) (a glycosaminoglycan; GAG) degradation enzymes, is a mucopolysaccharidosis (MPS), which is also known as MPS type III, and is characterized by subtypes A, B, C, and D, depending on identity of the dysfunctional enzyme. The lack of activity or low residual activity of an HS-degrading enzyme leads to excess HS in the cells, impairing the functions of different types of cells, including neurons. The disease usually leads to serious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 75 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…The likelihood of potential adverse effects is deemed minimal [334]. Rintz et al demonstrated that the administration of 50 mg/kg/day of resveratrol for 12 weeks or longer improved neurological symptoms, autophagy in the brain and liver, and decreased urinary GAG levels in an MPS IIIB mouse model [336]. Given the evidence that oxidative stress and compromised autophagy are implicated in the augmentation of inflammatory processes in a spectrum of lysosomal disorders, it would be prudent to investigate the efficacy of resveratrol in various forms of MPS.…”
Section: Anti-oxidant Drugsmentioning
confidence: 99%
“…The likelihood of potential adverse effects is deemed minimal [334]. Rintz et al demonstrated that the administration of 50 mg/kg/day of resveratrol for 12 weeks or longer improved neurological symptoms, autophagy in the brain and liver, and decreased urinary GAG levels in an MPS IIIB mouse model [336]. Given the evidence that oxidative stress and compromised autophagy are implicated in the augmentation of inflammatory processes in a spectrum of lysosomal disorders, it would be prudent to investigate the efficacy of resveratrol in various forms of MPS.…”
Section: Anti-oxidant Drugsmentioning
confidence: 99%
“…Antiviral activity inhibiting virus entrance in cells and viral replication through different mechanisms was observed as well as an adjuvant in the anti-COVID-19 therapy (Domi et al, 2022). Interestingly, the use of resveratrol on lysosomal storage diseases (LSDs), such as Sanfilippo disease (mucopolysaccharidosis type III [MPS III]), was proposed as a novel therapeutic approach in pathology (Paciotti et al, 2017;Rintz et al, 2023).…”
Section: Introductionmentioning
confidence: 99%